Improvement of aerodynamic performance of a small wind turbine. Issue 1 (February 2020) - Khalil, Yassine; Tenghiri, Lhoussaine; Abdi, Farid; Bentamy, Anas
The aerodynamic performance of horizontal-axis wind turbines is strongly dependent on many parameters, among which the airfoil type and the blade geometry (mainly defined by the chord and the twist distributions) are considered the most critical ones. In this article, an approach giving the appropriate airfoil for a small wind turbine design was conducted by performing an aerodynamic improvement of the blade's airfoil. First, a preliminary design of the rotor blades of a small wind turbine (11 kW) was conducted using the small wind turbine rotor design code. This preliminary approach was done for different airfoils, and it resulted in a maximum power coefficient of 0.40. Then, the aerodynamic efficiency of the wind turbine was improved by modifying the geometry of the airfoils. This technique targets the optimization of the lift-to-drag ratio (Cl/Cd) of the airfoil within a range of angles of attack. Also, a non-uniform rational B-spline approximation of the airfoil was adopted in order to reduce the number of the design variables of the optimization. This methodology determined the best airfoil for the design of a small wind turbine, and it gave an improved power coefficient of 0.42.